(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the concept of word combinations in the English language, their types, and their crucial role in effective communication. It includes insights from linguists and researchers, illustrating how free combinations, collocations, and set expressions facilitate natural speech and writing. Understanding word combinations enhances fluency, comprehension, and accuracy in both spoken and written English. Practical tips and exercises for learners are pr0vided to encourage confident and correct use of these combinations in real-life situations.